Local signal processing of the ALICE transition radiation detector at LHC (CERN) - Gutfleisch, Marcus (2005)
The transition radiation detector of the heavy ion experiment ALICE at LHC (CERN) integrates parts of the data acquisition and trigger system. Therefore, a multi chip module has been developped which incorporates two microchips. Detector signals are preamplified and shaped (Preamplifier and Shaper Chip, PASA). Thereafter they are converted from analog to digital and are processed (Tracklet Processing Chip, TRAP). This thesis describes the digital signal processing of the TRAP chip. The input signals are filtered digitally. Then, they are analyzed by a preprocessor and four CPUs with respect to segments of tracks. The thesis covers the complete development from hardware design of filter and preprocessor, their calibration, programming of the CPUs, up to first application studies on a prototype system.
Keywords: CERN; Hochschulschrift